Production Management Of Sawi (Brassica Juncea L.) Farming In Waiheru Village, Ambon City - Sri Husna; Ir. M. Turukay; W.B. Parera (Cita konsultindo, 2023)
This research aims to determine production management of mustard greens farming. Sampling was carried out using the census method on 25 farmers. The data collected is in the form of primary and secondary data, descriptive data analysis to look at produvtion management. The result of the research show that the production management carried out by farmers in mustard greens farming is in the form of aaspect 1). Palnning includes land use, ose of seeds, fertilizers, pesticides, determining planting time, and sources of capital. Farming management is carried out using family labor. 2). Organization of mustard greens farming is related to the farmer’s responsibility in mananging business. Because the size of the bisiness land is mall, the farmer and his wife are in charge of managing ir from land processing to harvetst, 3). Aspects of implementation in mustard greens farming, farmens have implemented cultivation technology well, 4). Evaluation of this aspect has not been carried out properly.